Analisis Semiotika Nilai Persahabatan Pada Film Jumbo - Fitri, Amelia; Pratiwi, Yuly Rahmi (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2025)
The new era is closely related to audiovisual entertainment, including films. Films reflect human feelings and experiences, so semiotic analysis is important to examine the meaning of visual and verbal signs, including the value of friendship. The Indonesian animated film Jumbo, with nearly 8 million viewers in 30 days, presents a warm story that can be analyzed semiotically to understand the value of friendship as a meaningful emotional and social bond. The purpose of this study is to determine the value of friendship in the film Jumbo using Ferdinand De Saussure's Semiotics analysis. The method used in this study is qualitative with a descriptive approach. The results of the study entitled "Semiotic Analysis of Friendship Values ​​in the Film Jumbo with the Ferdinand de Saussure Approach", can be concluded that the film Jumbo displays the construction of friendship values ​​through the relationship between the signifier and the signified which appears in the form of visual, verbal, and gestural signs.